Kontribusi Pendidikan Terhadap Lahirnya Kekristenan Di Pulau Ndao, Kabupaten Rote Ndao, Nusa Tenggara Timur - Luji, Daud Saleh (EDULEAD: Journal of Christian Education and Leadership, 2024)
The purpose of this study is to reveal the background of the birth of Christianity on Ndao Island, Rote Ndao Regency, East Nusa Tenggara. The author uses a qualitative method with interview data collection techniques and documentation studies of 6 informants. The results of the study indicate that the people of Ndao Island really miss going to school because the king often comes to Rote Island and sees the education that has been opened by the Dutch. In 1918 schools began to be opened on Ndao Island by a Dutch Pastor named Geisler and a teacher from Delha, Rote Island. The teacher not only taught general lessons but also taught Bible stories and not only children who believed but a number of parents of students also believed in Jesus. During a visit to the school, Geisler led worship and baptized 90 adults and children as Christians. This event became a milestone in the birth of the first church on Ndao Island. Schools or education have become the gateway and have made a major contribution to the birth of the church or Christianity on Ndao Island.AbstrakTujuan dari penelitian ini adalah untuk mengungkapkan latar belakang lahirnya kekristenan di Pulau Ndao Kabupaten Rote Ndao Nusa Tenggara Timur. Penulis menggunakan metode kualitatif dengan teknik pengumpulan data wawancara dan studi dokumentasi terhadap 6 orang narasumber. Hasil penelitian menunjukan bahwa bahwa masyarakat Pulau Ndao sangat rindu untuk bersekolah karena raja sering datang ke Pulau Rote dan melihat pendidikan yang sudah mulai dibuka oleh Bangsa Belanda. Pada tahun 1918 sekolah mulai di buka di Pulau Ndao oleh seorang Pendeta Belanda bernama Geisler dan seorang guru dari Delha pulau Rote. Guru tersebut tidak saja mengajarkan pelajaran umum tetapi juga mengajarkan cerita alkitab dan bukan saja anak-anak yang percaya tetapi sejumlah orang tua dari murid pun menjadi percaya kepada Yesus. Dalam suatu kunjungan di sekolah Geisler memimpin ibadah dan membaptis 90 orang dewasa dan anak-anak menjadi orang kristen. Peristiwa ini menjadi tonggak sejarah lahirnya gereja pertama kali di Pulau Ndao. Sekolah atau pendidikan telah menjadi pintu masuk serta memberikan kontribusi besar bagi lahirnya gereja atau kekristenan di Pulau Ndao.